HUBUNGAN TINGKAT DEPRESI DENGAN KUALITAS TIDUR PADA LANSIA DI DUSUN SEMENHARJO SURUHKALANG JATEN - Sri Aminingsih; Tunjung Sri Yulianti; Taufiq Bondan Rahmawan (KOSALA : Jurnal Ilmu Kesehatan, 2014)
Abstract Background : From the discovery of many cases of depression in the elderly that leads to decreased quality of sleep to be suicidal at the thought of illness and old age who live alone. Purpose: of this study was to determine the correlation between depression and sleep quality in the elderly in Semenharjo Suruhkalang Karanganyar`. Methods : This study is analytical, research design and cross sectional correlation. The study subjects were elderly Semenharjo totaling 53 pearsons. Once the calculation is done using the formula, samples taken by 47 person. The sampling technique used was quota sampling technique. Results : Data obtained by survey methods, namely distributing questionnaires containing HRS-D (Hamilton Rating Scale for Depression) to determine the level of depression and 20 statements to determine the quality of sleep for each respondent. The data collected is then analyzed with the chi square test with p = 0.05. From the research found 5 levels of depression that no amount of 2 elderly depression (4.3%), mild levels of depression some 11 elderly (23.4%), moderate and severe levels of depression with the same result number 8 elderly (17.0% ), and the rate of severe depression once some 18 elderly (38.3%). Then for a good night's sleep quality showed some 23 elderly (48.9%), while the quality of sleep is not restful some 24 elderly (51.1%). Conclusion : After the chi square test, p obtained for 0,000 so that the value of P <0.05, meaning that Ha received so it can be concluded that there is a correlation between depression and sleep quality in elderly Semenharjo, Suruhkalang Karanganyar. Keywords: Depression and Quality Levels